SISTEM PENILAIAN NILAI RAPORT MENGGUNAKAN METODE EXTREME PROGRAMMING PADA MTS BAITUSSALAM KEDING SAMPI - Handayani, Yudiana Tutik; Zaen, Mohammad Taufan Asri; Saikin, Saikin (LPPM STMIK Lombok, 2022)
Processing of Raport MTs Baitussalam Kending Sampi still uses the conventional system. Actually, by using the existing system, namely Ms. Excel has met the needs. However, problems began to arise because by using Ms. Excel value processing takes a long time, is less efficient, less effective, and never prints out as report cards. In designing this system the researcher uses several research methodologies. For the data collection method, the researcher used the observation method and the interview method for students, academics and the head of study programs. As for the method of analysis, the method used is the PIECES method. In this research, a report card assessment system was developed using the EXTREME programming methodology. The system is used by 4 users, namely students, subject teachers, homeroom teachers, and school principals. The interface is built based on the applicable printed form. Based on the results of functional testing carried out by the black box method. Each feature can run properly and the system can manage student report card assessment data.